Supervision Model of the SMPN 1 Julok School Principal in Improving the Islamic Religious Education Teachers’ Performance - Basri, Basri (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2022)
Splay principals play a decisive and strategic role in education sector. They play multi-functional roles, not only as leaders and educators but also as motivators, supervisors, controllers, and administrators. In the context of educational supervision, the principal is a role model in conducting business services and providing assistance between employees and the leader. This s contributes to teaching and learning process to develop their abilities improve and enhance the teaching and learning process at school. This research applied field research with a qualitative approach. The method used was a descriptive analysis study. Results showed that the supervision model of the school principal of SMP Negeri 1 Julok in improving the Islamic Religious Education teachers’ performance emphasized on developing punctuality in various aspects, especially at the administrative level.